Cerebral cavernous malformation-1 protein controls DLL4-Notch3 signaling between the endothelium and pericytes - Schulz, Gerald Bastian; Fischer, Andreas (Stroke, 2015)
Background and Purpose: Cerebral cavernous malformation (CCM) is a neurovascular dysplasia characterized by conglomerates of enlarged endothelial channels in the central nervous system, which are almost devoid of pericytes or smooth muscle cells. This disease is caused by loss-of-function mutations in CCM1, CCM2, or CCM3 genes in endothelial cells, making blood vessels highly susceptible to angiogenic stimuli. CCM1- and CCM3-silenced endothelial cells have a reduced expression of the Notch ligand Delta-like 4 (DLL4) resulting in impaired Notch signaling and irregular sprouting angiogenesis. This study aimed to address if DLL4, which is exclusively expressed on endothelial cells, may influence interactions of endothelial cells with pericytes, which express Notch3 as the predominant Notch receptor. Methods: Genetic manipulation of primary human endothelial cells and brain pericytes. Transgenic mouse models were also used. Results: Endothelial cell-specific ablation of Ccm1 and Ccm2 in different mouse models led to the formation of CCM-like lesions, which were poorly covered by periendothelial cells. CCM1 silencing in endothelial cells caused decreased Notch3 activity in cocultured pericytes. DLL4 proteins stimulated Notch3 receptors on human brain pericytes. Active Notch3 induced expression of PDGFRB2, N-Cadherin, HBEGF, TGFB1, NG2, and S1P genes. Notch3 signaling in pericytes enhanced the adhesion strength of pericytes to endothelial cells, limited their migratory and invasive behavior, and enhanced their antiangiogenic function. Pericytes silenced for Notch3 expression were more motile and could not efficiently repress angiogenesis. Conclusions: The data suggest that Notch signaling in pericytes is important to maintain the quiescent vascular phenotype. Deregulated Notch signaling may, therefore, contribute to the pathogenesis of CCM.